The meaning of critical educational gerontology for research and practice - Małgorzata Malec Rawiński (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
The problem of old age is an attractive and interesting issue in context of ageing society. There are quite a lot of research done on the field of activity of seniors, theirs participation in different projects and workshops at University of the Third Age or seniors' clubs. However educational aspect of ageing and old age is not enough recognized on the scientific field. The ageing and old people are not noticeable as the educational potential still. The article reflects on the aspects of moving borders of old age and profits from learning in the old. The core of the article is the issue of critical educational gerontology and critical geragogy with reference to educational activities offered at the Universities of the Third Age in Wroclaw.